Broadband Adjustable Terahertz Absorption in Series Asymmetric Oval-Shaped Graphene Pattern - Sun, Jian-Zhong; Li, Jiu-Sheng (Frontiers in Physics, 2020)
We propose a broadband adjustable graphene absorber in terahertz regime. A prototype is designed to verify the terahertz absorption characteristics by a periodic array layer of series asymmetric oval-shaped graphene patterns on polyimide and bottom layer of metal plate. The absorber with 92% absorption and the bandwidth ranging from 3.39 to 5.96 THz is achieved. By changing the Fermi level of graphene, the bandwidth and absorption can be flexibly adjusted. The absorption is more than 92% in the range of 0 40° incident angle. Using these characteristics, the simple absorber has broad application prospects in the fields of filter and switch in terahertz region.